Pengaruh Akuntabilitas dan Kinerja Karyawan terhadap Kepercayaan Pembayar Zakat (Muzakki) pada Baznas Kota Padang - Safitri, Tiara; Deviani, Deviani; Sulaiman, Ahmad Rahbani (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to analyze the effect of accountability and employee performance on zakat payers' (muzakki) trust in BAZNAS Kota Padang. A quantitative approach was used, with primary data collected through questionnaires distributed to 126 individual muzakki respondents. Data analysis was conducted using multiple linear regression with SPSS version 27. The findings reveal that accountability has a significant positive effect on muzakki trust, indicating that enhanced transparency and responsibility in zakat management foster public trust. Employee performance also shows a significant positive effect, where the quality of service provided by employees increases muzakki's confidence in zakat institutions. Together, these independent variables explain 56.2% of the variance in muzakki trust. The study supports legitimacy theory, emphasizing the importance of transparency and professionalism in building social legitimacy. These findings provide practical implications for BAZNAS to continuously improve accountability and employee performance to strengthen muzakki trust.